Computer Upskilling Trainings and Teachers’ Technological Literacy: Basis for Technological Skills Enhancement Plan (American Journal of Arts and Human Science, 2024)
The study is deeply rooted in the Diffusion of Innovation Theory, focusing on educators’ adoption of computer upskilling training programs. Everett Rogers’ theory offers a comprehensive framework for understanding how new ideas and technologies are embraced, highlighting key factors that impact the adoption process. This research delves into the computer upskilling training and technological literacy of teachers, addressing seven main objectives: profiling respondents, evaluating their level of computer upskilling training, assessing their technological literacy, exploring the relationship between training and literacy, and designing a technology skills enhancement plan. Conducted in the First Legislative Districts of Misamis Oriental, the study surveyed 250 teachers during the 2023-2024 school year. Utilizing a descriptive research design and a custom questionnaire, statistical tools like mean, standard deviations, Spearman Correlation Test, and Kruskal Wallis Test were employed to analyze the data. The findings reveal a high level of technological literacy among educators, particularly in Microsoft Office and social media skills, with room for improvement in areas like video conferencing and graphic design. The study underscores the significance of continuous training and support for educators to boost their technological competencies, recommending tailored professional development initiatives and resources to enhance essential technology skills for effective teaching and learning.